Crack growth study under thermo-mechanical loads: parametric analysis for 2024 T3 aluminum alloy - Salmi Abdallah; Elajrami; Mohamed El-Amine Slimani (Fracture and Structural Integrity)
Due to their severe operating conditions, many industrial components are subjected to complex combinations of cyclic mechanical stresses and thermal pressures. These combinations are responsible for the initiation and propagation of fatigue cracks in these parts, which can lead to failure. Thus, the study of the fatigue strength of these parts in such conditions becomes essential because it allows us to predict the life and safety of components. This study examines the influence of the load ratio and temperature on the propagation rate of long cracks on the outer surface. The propagation of a fatigue crack in ABAQUS was therefore automatically simulated using an identified Paris law of 2024 T3 aluminum alloy. Therefore, the study of these components' fatigue resistance in such conditions becomes essential to predict the service life and safety of the components